Respuestas

  • Usuario de Brainly
2013-11-17T22:49:15+01:00
 \left \{ {{3x+4y=-10} \atop {7x-3y=-48}} \right.

 \left \{ {{y= \frac{-10-3x}{4} } \atop {7x- 3*\frac{-10-3x}{4} }=-48} \right.

{7x-  (\frac{-30-9x}{4})  }=-48}

({ \frac{4*7x}{4})-  (\frac{-30-9x}{4})  }= \frac{-48*4}{4}}

{28x}+30+9x  }=-192

37x=-192-30   ===> 37x = -222

x= \frac{-222}{37} = -6

Sustituimos en la ecuacion para obtener ``y´´:
3*(-6)+4y=-10

-18+4y=-10

4y =-10+18 = 8

y= \frac{8}{4} = 2

Resultado:
x = -6 ; y = 2


espero que te sirva
salu2!!